2008
DOI: 10.1002/jbt.20255
|View full text |Cite
|
Sign up to set email alerts
|

N‐nitrosodimethylamine changes the expression of glutathione S‐transferase in the liver of male mice: The role of antioxidants

Abstract: The present study investigated the protective effect of gossypol, selenium, zinc, or glutathione (GSH) against dimethylnitrosamine (DMN)-induced hepatotoxicity in the livers of male mice. The expression and the activity of glutathione S-transferase (GST), levels of GSH, and free radicals (malondialdehyde (MDA)), as well as the activity of glutathione reductase were determined after the treatment of mice for seven consecutive days with low or high doses of gossypol, selenium, zinc, or GSH. In experimental group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
4
1
Order By: Relevance
“…In addition, the level of GSH was increased after treatment of rats with all tested N-nitrosamines (Table 2). It is taught that increment in GSH might be due to induction of GSH synthase and gamma-glutamyltransferase [63–65]. However, in the present study, the increased level of GSH was found to be dependent on the activity of GR since the activity of GR was also potentially induced after treatment of rats with N-nitrosamines (Table 2).…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, the level of GSH was increased after treatment of rats with all tested N-nitrosamines (Table 2). It is taught that increment in GSH might be due to induction of GSH synthase and gamma-glutamyltransferase [63–65]. However, in the present study, the increased level of GSH was found to be dependent on the activity of GR since the activity of GR was also potentially induced after treatment of rats with N-nitrosamines (Table 2).…”
Section: Discussioncontrasting
confidence: 56%
“…N‐nitrosamines are mainly metabolized by cytochrome P450 2E1 at a greater extent in the liver than any other organs into more toxic alkylating agents that bind covalently with DNA and other macromolecules . The toxicity of the alkylating agents could be alleviated after induction of GST activity and enhancement of GSH levels . Therefore, inducers of GSTs are generally considered as protective agents against toxicity of various toxic compounds including N‐nitrosamines.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrosamines which include DMN and diethyl nitrosamine (DEN) have been widely reported to stimulate or initiate oxidative stress and tissue destruction via the production of free radicals, which are released during the metabolism of nitrosamines by the cytochrome P 450 enzymes, forming reactive electrophiles [ 62 , 63 ]. Due to the instability of these ROS, they attack the electron rich components of cell membranes, thereby destroying the cells and altering cellular functions [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%